PELANGGARAN TERHADAP PRINSIP FIRST TO FILE DALAM SISTEM PENDAFTARAN MEREK DI INDONESIA - Erika Belita Vinky (2023)
Brand as a form of intellectual property has an important role in conducting trade activities. The trademark registration system in Indonesia is subject to the First to File principle, meaning that trademark rights are granted to a person who first applies for trademark registration. However, in practice, there are still frequent cases of First to File principle violation in the trademark registration system in Indonesia. The types of studies conducted in this study are included in the study of normative juridical research with Statute Approach to the Law and Case Approach (Case Approach) conducted by examining Law No. 20 of 2016 on Trade Marks and Geographical Indications, Law and Human Rights Minister Regulation No. 12 of 2016 Menkumham Law and Regulation No. 67 of Regulation No. 67In 2016, the Central Jakarta District Court Decision Number: 55/Pdt. Sus-Brand/2020/PN Niaga.Jkt.Pst. The results of this study are: 1) In the Central Jakarta District Court Decision Number: 55/Pdt. Sus-Brand/2020/PN Niaga. Jkt. Pst., it is seen that between the Plaintiff's brand and the Defendant's brand meet the criteria for similarity basically, which should be rejected by the Minister. In the First to File principle, trademark registration shall grant the trademark owner exclusive rights without the intervention of the other party. 2) The basis for the consideration of the Panel of Judges in resolving brand disputes in the Central Jakarta District Court Decision Number: 55/Pdt. Sus-Brand/2020/PN Niaga.Jkt.Pst has complied with the provisions listed in the applicable law. In this case, it is seen that the Panel of Judges is considering proposing legal protection theory and legal certainty to the party who first registered the trademark, namely the Plaintiff as the first registrar (First to File).